Disparities in Functional Outcome After Intracerebral Hemorrhage Among Asians and Pacific Islanders - Nakagawa, Kazuma; King, Sage L.; Seto, Todd B.; Mau, Marjorie K. L. M. (Frontiers in Neurology, 2018)
Background: Disparities in outcome after intracerebral hemorrhage (ICH) among Asians, Native Hawaiians and other Pacific Islanders (NHOPI) have been inadequately studied. We sought to assess differences in functional outcome between Asians and NHOPI after ICH. Methods: A multiracial prospective cohort study of ICH patients was conducted from 2011 to 2016 at a tertiary center in Honolulu, HI to assess racial disparities in come after ICH. Favorable outcome was defined as 3-month modified Rankin Scale (mRS) score 2. Patients with no available 3-month functional outcome, race other than Asians and NHOPI, and baseline mRS >0 were excluded. Multivariable analyses using logistic regression were performed to assess the impact of race on favorable outcome after adjusting for the ICH Score, early do-not-resuscitate (DNR) order and dementia/cognitive impairment. Results: A total of 220 patients (161 Asians, 59 NHOPI) were studied. Overall, 65 (29.5%) achieved favorable outcome at 3 months. NHOPI were younger than Asians (p<0.0001), and had higher prevalence of diabetes (p=0.007), obesity (p<0.0001), and lower prevalence of dementia/cognitive impairment (p=0.02), early DNR order (p=0.0004) and advance directive presence (p=0.0005). NHOPI race was a predictor of favorable outcome in the unadjusted model (OR 2.47, 95% CI: 1.32–4.62) and after adjusting for the ICH Score (OR 2.30, 95% CI: 1.06–4.97) but not in the final model (OR 2.04, 95% CI: 0.94–4.42). In the final model, the ICH Score was the only independent negative predictor of outcome (OR 0.26, 95% CI: 0.17, 0.41 per point). Conclusions: NHOPI are more likely to achieve favorable functional outcome after ICH compared to Asians even after controlling for ICH severity. However, this association was attenuated by the DNR and dementia/cognitive impairment status.